Selected letters of William Empson - Empson, William, 1906-1984 (Oxford University Press, 2008)
All readers of literary history and criticism will benefit from this edition of letters by William Empson, one of the foremost writers and critics of the twentieth century. This correspondence shows him working out his ideas for all of his major books as well as complementary studies in writers including Shakespeare, Marlowe, Donne, Marvell, Coleridge, and Joyce. The edition also gives the fullest possible picture of his robust interactions with many other prominent writers, including the likes of F.R. Leavis, Helen Gardner, Frank Kermode, Christopher Norris, and I.A. Richards. - ;This edite.